2012
DOI: 10.1111/j.1529-8817.2012.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Macroalgal Chemical Extracts on Spore Behavior of the Antarctic Epiphyte Elachista antarctica Phaeophyceae

Abstract: Most macroalgal species along the Western Antarctic Peninsula (WAP) are defended against predation, many using chemical defenses. These subtidal communities are also mostly devoid of free living filamentous algae. However, one endo/epiphyte, Elachista antarctica, is found growing exclusively out of the palatable rhodophyte Palmaria decipiens. To understand this unusual and exclusive epiphytization, we tested whether macroalgal secondary metabolites such as those responsible for deterring sympatric grazers, aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Results show that the environmental modifications driven by the macroalgae appear to play a significant role in promoting distinct temporal and spatial patchiness in the microphytobenthos. However, we cannot disregard a biological response based on species specificity, as other factors such as chemical cues or deterrents may also influence microphytobenthic settlement and development (Lam et al 2008, Bucolo et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Results show that the environmental modifications driven by the macroalgae appear to play a significant role in promoting distinct temporal and spatial patchiness in the microphytobenthos. However, we cannot disregard a biological response based on species specificity, as other factors such as chemical cues or deterrents may also influence microphytobenthic settlement and development (Lam et al 2008, Bucolo et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Host defenses against endophyte infection may be present in Antarctic algae but are not thoroughly characterized. For instance, settlement of the filamentous epi/endophyte E. antárctica is inhibited by extracts of most sympatric macroalgae save its one known host P. decipiens (Bucolo et al 2012). Although the present study focuses on filamentous algal endophytes, fungal endophytes have also been reported in three species of Antarctic macroalgae (Loque et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…only develop the protective cell wall upon settlement (Braten 1971). On the other hand, since algal spores can be repelled by a number of chemical stimuli (Bucolo et al 2012), the CCA's inhibitory component can act as a negative cue, preventing spore settlement until death ensues (Egan et al 2001b). There are only few studies regarding CCA allelopathy against seaweed spores, most of them on temperate CCA; our results are similar to those found in temperate studies (Table 4).…”
Section: Effects Of Cca-associated Microbes On Seaweed Settlementmentioning
confidence: 99%